The “Good” Limb Makes the “Bad” Limb Worse: Experience-Dependent Interhemispheric Disruption of Functional Outcome After Cortical Infarcts in Rats. - Allred, Rachel P.; Cappellini, Colleen H.; Jones, Theresa A. (Behavioral Neuroscience, 2010)
Following stroke-like lesions to the sensorimotor cortex in rats, experience with the ipsi-to-lesion (ipsilesional), “nonparetic”, forelimb worsens deficits in the contralesional, “paretic”, forelimb. We tested whether the maladaptive effects of experience with the nonparetic limb are mediated through callosal connections and the contralesional sensorimotor cortex. Adult male rats with proficiency in skilled reaching with their dominant (for reaching) forelimb received ischemic bilateral sensorimotor cortex lesions, or unilateral lesions, with or without callosal transections. After assessing dominant forelimb function (the paretic forelimb in rats with unilateral lesions), animals were trained with their nonparetic/nondominant forelimb or underwent control procedures for 15 days. Animals were then tested with their paretic/dominant forelimb. In animals with unilateral lesions only, nonparetic forelimb training worsened subsequent performance with the paretic forelimb, as found previously. This effect was not found in animals with both callosal transections and unilateral lesions. After bilateral lesions, training the nondominant limb did not worsen function of the dominant limb compared with controls. Thus, the maladaptive effects of training the nonparetic limb on paretic forelimb function depend upon the contralesional cortex and transcallosal projections. This suggests that this experience-dependent disruption of functional recovery is mediated through interhemispheric connections of the sensorimotor cortex. Reprinted by permission of the publisher.